Perspectives of Presynaptic Autoreceptors and Presynaptic Heteroreceptors in the Mechanism of Neurotransmission - Gawade, Shivaji Prataprao (Indian Journal of Pharmaceutical Education and Research, 2022)
The presynaptic autoreceptors and / or presynaptic heteroreceptors of the principal neurotransmitters involved in the release mechanism of neurotransmission have been identified employing various experimental models, based on receptor types / receptor subtypes and it’s stimulatory or inhibitory functions. The pharmacological, neurophysiological, neurobiochemical in vivo or in vitro insect, animal or human prototype experimental models were selected from the exhaustive search of literature published in standard journals using, Google search engine, to identify the presynaptic autoreceptors or presynaptic heteroreceptors. The complexity of neuronal function in nervous system is based on the expression of presynaptic autoreceptors controlling / regulating the release and that of presynaptic heteroreceptors activated by the neurotransmitter / modulator released from other axon terminal communicated inter/ intraneuronally. In the present review, eight types of prominent presynaptic auto or heteroreceptors of seven neurotransmitters of central and peripheral nervous system namely cholinergic muscarinic, cholinergic nicotinic, adrenergic, serotonergic, dopaminergic, histaminergic, glutaminergic and GABArgic and their subtypes were classified according to stimulatory or inhibitory functions and explained on the basis of prototype experimental in vitro / in vivo tissue models.
Keywords: Presynaptic; Autoreceptors; Heteroreceptors; Neurotransmitter; Tissue models; Neuronal functions